Social comparison: when social media mirror body image among female adolescents in Karawang regency - Anggraeni, Sheli; Muharsih, Lania; Maulidia, Ananda Saadatul (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study aims to examine the influence of social comparison on body image of female adolescents, who are active social media users, in Karawang Regency. The population of the study was infinite. The sample consisted of 204 female adolescents aged 12-22 years who actively used Instagram and TikTok, selected using the convenience sampling technique. The study was conducted using a quantitative approach with a causal design. The data were collected using two psychological scales: the 13-item Body Image Scale adapted from Khairani et al. (2019) and the 11-item Physical Appearance Comparison Scale-Revised (PACS-R) adopted from Rachmat et al. (2024). The data were analyzed using the simple linear regression. Results showed that social comparison significantly influenced body image (p=0.017); p<0.05), indicating that higher tendency for self-comparison leads to poorer body image. The R² value of 2.8% indicates that social comparison is a contributing factor, while the remaining 97.2% of the variance may be attributed to other factors not explored in this study.